Pemberdayaan Masyarakat Melalui Pelatihan Membuat Makanan Olahan Dari jantung Pisang Untuk Kelancaran Produksi ASI di Link. Temu Putih Kota Cilegon Tahun 2024 - Lufar, Nay; Ismawati, Iis (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2024)
Breast milk is the primary and most essential food for newborn babies aged 0-6 months. Several factors can affect the amount of breast milk production, including nutritional patterns, support, breast care, baby's sucking, and socio-cultural factors. It is important to understand the nutritional factors for breastfeeding mothers because their nutritional needs must be increased to enhance breast milk production. One effort to boost breast milk production is through the consumption of foods that influence lactation, such as banana blossom preparations. The dietary fiber in banana blossoms is beneficial for increasing milk production because it contains lactagogum, which has the potential to stimulate oxytocin and prolactin hormones. These components, such as alkaloids, polyphenols, steroids, flavonoids, and other substances, are effective in enhancing and facilitating breast milk production. The purpose of this community service, in the form of training to make food preparations from banana blossoms, is to empower the community, particularly pregnant and postpartum women, by enhancing their skills in utilizing banana blossoms as a food that can be processed to increase breast milk production. This community service is carried out by providing training on how to make banana blossom-based food, specifically turning it into nuggets, for pregnant and postpartum women in the Temu Putih area, Cilegon City.